Trophic level and position of Pterygoplichthys pardalis in Ciliwung River (Jakarta, Indonesia) ecosystem based on the gut content analysis - Dewi Elfidasari; Fahma Wijayanti; Afifatus Sholihah (Society for Indonesian Biodiversity, 2020)
Abstract. Elfidasari D, Wijayanti F, Sholihah A. 2020. Trophic level and Position of Pterygoplichthys pardalis in Ciliwung River (Jakarta, Indonesia) ecosystem based on the gut content analysis. Biodiversitas 21: 2862-2870. The trophic level of an organism describes its sequence of natural diet visible to the food chain along with its ecosystem. This is also related to the type of diet composition and food fraction obtained by analyzing its gut content. The Pterygoplichthys pardalis from Ciliwung River show the diversity of the natural diet. The aims of this study is to determine the trophic level and position of P. pardalis in the Ciliwung River ecosystem based on gut content analysis using the purposive sampling method. Data were obtained from a total of 30 fishes from the Kalibata and Cawang areas through observations. The fishes were dissected, and gut contents were observed using a light microscope, with observations repeated 5 times of each sample. Data analysis includes relative length of gut, Index of Preponderance, area of the diet niche, niche area, niche overlap, and trophic level of an organism. The results showed that P. pardalis in Ciliwung River is at trophic level II, and included as herbivores (2.00 < troph < 2.90) that consist of Bacillariophyta (82.03%), Chlorophyta (12.7%), Cyanophyta (3.74%), Euglenophyta (1.19%), Amoebozoa (0.28%), and Dinoflagellata (0.68%).